Pengaruh Good Corporate Governance Dan Leverage Terhadap Kinerja Keuangan (Studi Kasus Sektor Perbankan Tahun 2018-2020) - Luthfi Arief Prayoga; Nurhidayah Nurhidayah; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Currently, the development of banks is increasingly rapid and a high degree of complexity can affect the operation of the bank. The high complexity of the banking business increases the risks that banks in Indonesia face. Banking is an industry that in its business relies on the trust of the public, so the soundness of the bank must be maintained. According to a World Bank survey, the implementation of corporate governance systems is weak or generally known as good corporate governance. has not been maximized in the implementation process. The implementation of good corporate governance system has not been effective or effective because many cases still occur such as: money laundering, embezzlement, theft and corruption carried out by unscrupulous banks themselves. still happening in Indonesia. Financial performance management in the banking sector To know and analyze the role of leverage on financial performance in the banking sector, quantitative research is a type of research with technical characteristics systematic, well-planned and clearly structured end-to-end study design. This study used a data-documentation approach, namely by collecting data from a variety of identified sources. Data on banking and financial statements are obtained from the official website of the Indonesian Stock Exchange. The results of the trials carried out can be described in depth in relation to the results of the research carried out, and also on the basis of the results of the tests carried out they can be made in relation to the results of the studies carried out. regarding the presentation of the results. Based on the research conducted, it can be concluded that good corporate governance using the variables of organizational ownership and manager ownership does not have a significant effect on financial performance, leading to concluded that good corporate governance and leverage variables have a significant effect on financial performance. Keywords: Good Corporate Governance, Leverage, Financial Performance